P268 What Kind Of Evidence Supported The Clinical Practice Guideline For The Syndromic Management Of Sexually Transmitted Infections And Other Infection Of The Genital Tract 2012. (15th August 2013) - Gaitan, H; Torres, M; Rodriguez, A
Abstract : Background: In recent years, the GRADE approach has been broadly accepted by many GDG. There is a lack of information about the relationship between the types of evidence with the strength of recommendations using GRADE. Objective: To present the evidence mapping of the literature used to develop recommendations in the Guideline for Syndromic management of the Genital Tract Infections. Methods: The evidence of each recommendation was reviewed and was classified according to the type, quality and quantity of evidence and strength of the recommendation. A descriptive analysis was performed as well as a cross-analysis to find out the relationship between the strength of the recommendation and the underlying quality of the evidence. Results: 80 recommendations were identified. Systematic reviews supported the 29.1% of the recommendations, RCT 25.6%, observational studies 5.9%, guidelines 9.3% and expert opinion 30.1%. The quality of the evidence was high (14%), moderate (15%), low (16%) and very low (55%). 63.7% of the recommendations were strong in favour. 14% of the strong recommendations came from high quality evidence and 49% came from very low quality evidence. Discussion: The evidence shows a similar percentage of systematic reviews, RCT and expert opinion in the guideline. Despite the quality of the evidence, the number of strong recommendations is high due to the other criteria of the GRADE approach. Implications for Guideline Developers: The GRADE approach allows weighting other factors beyond the quality of the evidence. Research needs to be done on the most important factors in grading the recommendations.